Calmodulin: A Multitasking Protein in Kv7.2 Potassium Channel Functions - Alessandro Alaimo; Alvaro Villarroel (Biomolecules, 2018)
The ubiquitous calcium transducer calmodulin (CaM) plays a pivotal role in many cellular processes, regulating a myriad of structurally different target proteins. Indeed, it is unquestionable that CaM is the most relevant transductor of calcium signals in eukaryotic cells. During the last two decades, different studies have demonstrated that CaM mediates the modulation of several ion channels. Among others, it has been indicated that Kv7.2 channels, one of the members of the voltage gated potassium channel family that plays a critical role in brain excitability, requires CaM binding to regulate the different mechanisms that govern its functions. The purpose of this review is to provide an overview of the most recent advances in structure–function studies on the role of CaM regulation of Kv7.2 and the other members of the Kv7 family.